Employment dynamics in rural Europe [ - Post, Jaap H.; Terluin, Ida J. (CABI, 2000)
A comparative analysis of rural employment dynamics in leading and lagging rural regions in the EU member states during the last two decades is presented. A theoretical framework for the analysis of employment development in rural regions is discussed ad a statistical analysis of socioeconomic characteristics of all EU regions is presented. Detailed case studies of pairs of leading and lagging rural regions in nine EU member states (Germany, Greece, Spain, France, Italy, Netherlands, Austria, Belgium, Finland) are presented. Key messages for employment creation in rural regions are identified.